3(5x+1)+6(5x+1)=2

Simple and best practice solution for 3(5x+1)+6(5x+1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+1)+6(5x+1)=2 equation:


Simplifying
3(5x + 1) + 6(5x + 1) = 2

Reorder the terms:
3(1 + 5x) + 6(5x + 1) = 2
(1 * 3 + 5x * 3) + 6(5x + 1) = 2
(3 + 15x) + 6(5x + 1) = 2

Reorder the terms:
3 + 15x + 6(1 + 5x) = 2
3 + 15x + (1 * 6 + 5x * 6) = 2
3 + 15x + (6 + 30x) = 2

Reorder the terms:
3 + 6 + 15x + 30x = 2

Combine like terms: 3 + 6 = 9
9 + 15x + 30x = 2

Combine like terms: 15x + 30x = 45x
9 + 45x = 2

Solving
9 + 45x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 45x = 2 + -9

Combine like terms: 9 + -9 = 0
0 + 45x = 2 + -9
45x = 2 + -9

Combine like terms: 2 + -9 = -7
45x = -7

Divide each side by '45'.
x = -0.1555555556

Simplifying
x = -0.1555555556

See similar equations:

| .8m-.2m=9 | | 2x^4-3x^3+2x^2-15x+14=0 | | u^2-6u+8=0 | | -32xy^5+40x^3y^5-16xy^5= | | 8y=7y-45 | | 3t^3-9t+6=0 | | 27c^4-125c=0 | | 9x^2-5x=3 | | -8=-x-4 | | 3x=2-4y | | 10y=5y-5 | | 4(3x+4)=52 | | 35x^2-16x-3=0 | | 4x+3=-45 | | 9x+14=-67 | | w^2+4w-x^2+4=0 | | -7y+5(y-4)=-18 | | 6x+13=-5 | | 2x-0.35=.20 | | 4x+6=-62 | | 7(4x+1)=3(12x-3) | | 92x+31=72 | | -3x+9=30-6x | | 2c/10=24 | | (5c+6)(5c-6)=0 | | 2x^2-4x-44=0 | | 53a-143=42a+8 | | 3x=6-x | | 18-t/20=-9 | | 3s/5=-21 | | x^2-15x+9=0 | | n(n-6)=7 |

Equations solver categories